Prevention Health Education Acute Respiratory Tract Infections - Sari, Yulia Indah Permata; Martawinarti, Rts. Netisa; Juniana, Maolia; Lukman, Muhammad Nasril; Santi, Lala Delva; Aulia, Esa Surya; Santhi, Fera Afri; Amalia, Mita; Agustina, Rati Elvi; Komala, Rossie Intan; Harnum, Assyafiah; Azizi, Putri Dwi (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Acute Respiratory Infection (ARI) is the most common infectious disease causing morbidity and mortality worldwide. The prevalence rate of ARI in Indonesia is 9.3%. Prevalence of ARI based on the diagnosis of health workers in Jambi Province was 5.5%, while the prevalence of ARI in Jambi City was 6.25%. One of the efforts that can be made to reduce ARI transmission is to increase knowledge about ARI prevention. Increasing knowledge can be done through health education activities. This community service aims to provide information about ARI disease. This activity utilized slide and leaflet media and was attended by 25 participants. It is hoped that the results of this activity can be useful for participants to prevent ARI disease.